Stock Exchange Governance and Market Quality - KRISHNAMURTI, Chandrasekhar (Institutional Knowledge at Singapore Management University, 2003)
We show that organization structure of a stock exchange matters by utilizing the unique setting prevailing in India. India has two major stock markets, the Bombay Stock Exchange (BSE) and the National Stock Exchange (NSE). These two exchanges adopt similar trading systems, trade essentially identical stocks, and follow the same trading hours. However, these exchanges have different organizational structures: BSE is mutualized whereas NSE is demutualized. Using the Hasbrouck [Review of Financial Studies 6 (1993) 191] measure of market quality we show that NSE provides a better quality market than BSE. This result is consistent with the work of Domowitz and Steil [Brookings-Wharton Papers on Financial Services, 1999], who proposed that demutualized exchanges are superior to mutualized in governance.